Decision-Making and Relationship Competence When Reporting Suspected Physical Abuse and Child Neglect: An Objective Structured Clinical Evaluation - Tufford, Lea (Clin Soc Work J, 2021)
Mandatory reporting of suspected child abuse and neglect highlights the challenges between the ethical and legal obligations of social workers and the need to maintain the therapeutic relationship with the client. The ability to bridge this tension is paramount to ensure continued psychosocial treatment and the well-being of children. This paper discusses a study to determine the decision-making factors of social work students and practitioners when facing a suspicion of child abuse and neglect, how they justify their decision to report or not report to child protection services, and the current and future relationship repair strategies used with simulated clients during an objective structured clinical evaluation (OSCE). Nineteen BSW, MSW, and experienced practitioners (N = 19) underwent an OSCE with one of two child maltreatment vignettes, physical abuse or neglect. Fisher’s exact test was used to examine participants’ historical and current reporting behaviors. Independent samples T-tests, Cohen’s D, and qualitative content analysis was used to examine participants’ decision making and relationship repair strategies when faced with suspected child abuse and neglect. Results showed that six participants discussed the duty to report during the OSCE while 13 participants did not. Participants’ who discussed and did not discuss the duty to report during the OSCE articulated clear reasons for their decision and identified relationship repair strategies in working with the client. A sub-group of participants who identified the child maltreatment but did not discuss the duty to report, provided more tentative and complex reasons for their inaction and next steps in working with the client. All participants demonstrated a degree of competence and critical reflection in the OSCE, with integration for future learning. These findings are discussed and implications for future practice are offered.